Pembiasaan Sholat Dhuha dalam Membentuk Karakter Disiplin Santri (Studi Kasus Ponpes Darun Najah Semen Kediri) - M. Musthofa Asy'ari (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
Discipline is something that is easy to say, but can be difficult to do. You need strong determination and efforts to train yourself to become a person with a disciplined character. Discipline is also something that is very important, including for a student. Students who recite the Koran with discipline or seriously, God willing, will be closer to success. Because the character of discipline is so important, it needs to be instilled in the students. Because the basic nature of most humans is that they like to relax and feel reluctant to do hard things. The aim of this research is firstly to explain the model of habituation to Duha prayer at the Darun Najah Islamic Boarding School, Sem Kediri, secondly, to explain the correlation between the habituation to Duha prayer and the disciplinary character of Santi Islamic Boarding School, Darun Najah Semen Kediri. The approach in this research is a qualitative method, with the research location at Pon Pes Darun Najah Semen, Kediri Regency. The main source used in this research is words and the remaining actions are additional data such as documents etc. The results of this research are 1) The Duha prayer at Pon Pes Darun Najah is carried out at the beginning of each day, namely 07:00 WIB. This is intended so that students start their activities at school by always remembering Allah. Apart from that, the movements carried out during the Dhuha prayer can also have a fitness effect, which in turn will bring a special enthusiasm to the students' (body) when participating in teaching and learning activities in class. And in this way, it is hoped that students will be able to absorb the lessons taught in class better. 2) the habit of performing Dhuha prayers in congregation at Pon Pes Darun Najah has a positive impact on the disciplined character of the students. This is of course achieved provided that the dhuha prayer is carried out continuously and seriously. Pay attention to the implementation time, as well as monitoring and evaluating the implementation of the Dhuha prayer by the students.